Is STEM classroom the appropriate learning environment where students can achieve their learning objectives? (NPRC Journal of Multidisciplinary Research, 2025)
The Fourth Industrial Revolution (Industry 4.0) has brought transformative changes to daily life, necessitating adaptations in educational systems to meet new technological and societal demands. This article explores STEM (Science, Technology, Engineering, and Mathematics) education as a viable approach to equipping students with essential 21st-century skills, focusing on the learning environment's role in achieving these goals. Through documentary research, the study analyzes the key components of an effective learning environment—organization and classroom dynamics—and evaluates whether STEM classrooms fulfill these criteria. Findings suggest that STEM education fosters flexibility, interdisciplinary problem-solving, collaboration, and creativity, aligning with the principles of an optimal learning environment. The teacher's role shifts to that of a facilitator, guiding students through inquiry-based learning while promoting motivation, communication, and critical thinking. The study concludes that STEM classrooms provide a conducive setting for developing the skills needed in an evolving workforce, supported by pedagogical strategies that emphasize real-world applications and student-centered learning.